INOVASI E-GOVERNMENT APLIKASI BERBASIS PENDATAAN KELUARGA SATU PINTU CARIK JAKARTA DALAM PENGUMPULAN DATA KOMPREHENSIF KELUARGA OLEH DASAWISMA - Arsy, Talitha Firda; Hakim, Lukmanul; Kurniansyah, Dadan (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2026)
Family data, which is important but has not been optimally managed and remains scattered, is needed by the DKI Jakarta Provincial Government for comprehensive and accurate insights into family conditions; therefore, an e-government innovation called the Carik Jakarta application was created. This study aims to analyze the innovation in the Carik Jakarta application using Rogers' Innovation Attribute Theory framework. The method used is qualitative with data collection techniques of observation, interviews, documentation studies, and literature studies. The results of the study show that the success of the Carik Jakarta innovation is determined by improving the efficiency, accuracy, transparency, and accountability of data, as well as its compatibility with the previous data collection mechanisms that have been digitized and integrated. The main obstacles to innovation lie in the limited digital literacy of some Dasawisma cadres, technical constraints of the application, and the low level of visibility of direct benefits to the community. The gradual trial and piloting process played an important role in supporting the adoption of innovation. This study provides empirical and practical contributions to e-government innovation studies related to the need to strengthen human resource capacity, system stability, and data-based family policy socialization strategies.